Quantitative sequencing of 5-formylcytosine in DNA at single-base resolution - Booth, Michael J. (2014)
The cytosine modifications 5-hydroxymethylcytosine (5hmC) and 5-formylcytosine (5fC) were recently found to exist in the genomic DNA of a wide range of mammalian cell types. It is important to now understand their role in normal biological function and disease. Here we introduce reduced bisulfite sequencing (redBS-Seq), a method to quantitatively decode 5fC in DNA at singlebase resolution, based on a selective chemical reduction of 5fC to 5hmC followed by bisulfite treatment. Following extensive validation on synthetic and genomic DNA, we combined redBS-Seq and oxidative bisulfite sequencing (oxBS-Seq) to generate the first combined genomic map of 5-methylcytosine, 5hmC and 5fC in mouse embryonic stem cells. Our experiments revealed that 5fC is present at relatively high levels in certain genomic locations, in comparison to 5hmC and 5mC. The combination of these chemical methods can quantify and precisely map these three cytosine derivatives in the genome and will help provide insights into their function.